Pemberdayaan Ekonomi Masyarakat Berbasis Perkebunan Kelapa - Puturuhu, Diana; Soselissa, Hendry Ch.; Tanamal, Johan (Public Policy, 2023)
This study aims to determine the efforts to empower coconut farmers in increasing people's in the Gale-Gale Administrative Country and the obstacles faced in terms of empowering coconut farmers. The research method uses descriptivemethods using qualitative data types. Data collection techniques were carried out by means of observation, interviews and documentation. The data analysis method was carried out starting from data collection, data reduction, data presentation and drawing conclusions. The results of the study indicate that the empowerment efforts carried out by the government or related agencies have not been maximized and the income obtained by farmers from coconut processing is still low. There are several things that become obstacles in empowering coconut farmers, one of which is the lack of awareness of coconut farmers to innovate on processed coconut products so that they can develop not only stop at copra and charcoal containers. This is due to the limited competence possessed by farmers ranging from education, skills, and insight so that development is slow and income is still low.